Effect of augmented reality navigation technology on perioperative safety in partial nephrectomies: A meta-analysis and systematic review - Cheng, Cong; Lu, MaCheng; Zhang, Ye; Hu, XingQian (Frontiers in Surgery, 2023)
Aim: To evaluate the impact of augmented reality surgical navigation (ARSN) technology on short-term outcomes of partial nephrectomy (PN). Methods: A systematic literature search was conducted in PubMed, Embase, Cochrane, and Web of Science for eligible studies published through March 28, 2022. Two researchers independently performed the article screening, data extraction and quality review. Data analysis was performed using Cochrane Review Manager software. Results: A total of 583 patients from eight studies were included in the analysis, with 313 in the ARSN-assisted PN group (AR group) and 270 in the conventional PN group (NAR group). ARSN-assisted PN showed better outcomes than conventional surgery in terms of operative time, estimated blood loss, global ischemia rate, warm ischemia time, and enucleation rate. However, there were no significant differences in the rate of Conversion to radical nephrectomy (RN), postoperative estimated glomerular filtration rate (eGFR), positive margin rate, and postoperative complication rate. Conclusion: The utilization of ARSN can improve the perioperative safety of PN. Compared with conventional PN, ARSN-assisted PN can reduce intraoperative blood loss, shorten operative time, and improve renal ischemia. Although direct evidence is lacking, our results still suggest a potential advantage of ARSN in improving renal recovery after PN. However, as the ARSN system is still in an exploratory stage, its relevance in PN have been poorly reported. Additional high-quality randomized controlled trial (RCT) studies will be required to confirm the effect of ARSN on PN.